A Strategi Digitalisasi Berbasis Media Sosial Dalam Pemasaran Produk UMKM Mamin Di Nusa Tenggara Barat - Baiq Desthania Prathama; Dwi Arini Nursansiwi; Armiani, Armiani (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This study aims to explore digitalization strategies in optimizing the use of social media to increase competitiveness and sales of Micro, Small and Medium Enterprises (MSMEs) in the food and beverage sector (MaMin) in West Nusa Tenggara (NTB). In the post-pandemic business landscape and the Industrial Revolution 4.0, digitalization has become a strategic necessity, but its utilization has not been maximized among NTB MSMEs. Using a qualitative approach through in-depth interviews with nine respondents consisting of MaMin MSME players, this study explores the strategic dimensions of digital adoption, patterns of social media utilization, and constraints and potentials of digital transformation at the grassroots level. The grand theory used is the Resource-Based View (RBV) to understand how digital capabilities as unique resources create competitive advantage. The results found five main digitalization strategies: digital literacy, product visualization content, customer interaction, platform integration, and social media algorithm trend adaptation. This study offers practical and theoretical contributions in the development of a digitalization strategy model based on locality and digital culture of regional MSMEs.